Risk Factors for the Occurrence of Depressive Disorders in Pediatric Patients With Tuberculosis - Mihailov OM; Stavar Matei L; Tocu G; Ciubara A; Mihailov R (Pediatric Health, Medicine and Therapeutics)
Oana Mariana Mihailov,1,2 Loredana Stavar Matei,2 George Tocu,3 Anamaria Ciubara,2 Raul Mihailov4 1Children Pneumology Department, Pneumophthisiology Hospital “Sfântul Spiridon” of Galati, Galați, 800198, Romania; 2Clinical Medicine Department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University of Galati, Galați, 800008, Romania; 3Pharmaceutical Science Department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University of Galati, Galați, 800008, Romania; 4Clinical Surgery department, Faculty of Medicine and Pharmacy, “dunărea de Jos” University of Galati, Galați, 800008, RomaniaCorrespondence: George Tocu, Pharmaceutical science department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University of Galati, Galați, 800008, Romania, Tel +40773819438, Email george.tocu@ugal.roBackground: Tuberculosis (TB) is one of the oldest and most persistent infectious diseases, continuing to pose a significant public health challenge worldwide. Children diagnosed with TB are particularly vulnerable to developing depressive disorders, which can significantly reduce their quality of life and negatively affect treatment adherence and recovery. This study aimed to identify risk and prognostic factors associated with depressive disorders in pediatric patients diagnosed with tuberculosis through a prospective analysis.Materials and Methods: A prospective study was conducted on 190 pediatric patients, aged 7 to 18 years, diagnosed with tuberculosis and treated at the Pneumophthisiology Hospital in Galați, Romania, between 2019 and 2021. The CDI (Children’s Depression Inventory) was administered to assess depressive symptoms over the course of the study.Objective: The study aims to determine the prevalence of depressive disorders in children and adolescents by analyzing risk factors such as age, gender, place of origin, and access to medical services, as well as the effectiveness of CDI as a diagnostic tool. It also seeks to correlate clinical and demographic data with CDI scores and evaluate changes over time to identify solutions that support early diagnosis and intervention.Results: Out of the initial 190 patients, 158 completed the CDI, as some did not return for follow-up evaluations or declined to participate. Of these, 146 (92.4%) demonstrated clinically significant depressive symptoms. Key risk factors for depressive disorders included a rural background, male gender, and age between 15 and 18 years.Conclusion: Specific risk factors and vulnerabilities contribute to the development of depressive disorders in pediatric TB patients. Early identification and monitoring of these factors in a prospective framework are essential for improving the prognosis of both depression and tuberculosis, ultimately enhancing the overall outcomes for affected children.Keywords: children’s depression inventory, pediatric depression, tuberculosis, risk factor